Analisis usaha industri kecil di Kabupaten Kerinci Provinsi Jambi (studi kasus industri kecil pengolahan sirup kayu manis di Kabupaten Kerinci) - Ekang Ardianto; Etik Umiyati; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2018)
This study aims to analyze: 1) the characteristics of cinnamon syrup entrepreneurs; 2) factors affecting the production of cinnamon syrup and 3) the prospect of developing the cinnamon syrup industry in Kerinci Regency. The data used are primary data based on surveys of cinnamon syrup entrepreneurs. Data were analyzed descriptively, multiple regression analysis and SWOT analysis. The results of the study found: 1) The age of cinnamon syrup entrepreneurs is generally in the productive age. The education level of cinnamon syrup entrepreneurs is relatively good. More than half (60.00 percent) have high school education and above. The average income of cinnamon syrup entrepreneurs in Kerinci Regency is Rp. 22,833,333 per year; 2) The factors that significantly influence the production of cinnamon syrup in Kerinci Regency are raw materials and capital, while the workforce and the frequency of coaching do not have a significant effect; 3) Based on the SWOT analysis, the cinnamon syrup industry in Kerinci Regency has good prospects to develop